#TransformFFA: An Analysis of Social Media Content During the 2016 National FFA Convention - Tiffany M. Rogers-Randolph; Lisa K Lundy; Jessica L Harsh; Raychel Rabon (Journal of Applied Communications, 2018)
The proliferation of social media has the ability to considerably impact stakeholders’ perspective of an organization’s brand. Due to this relationship, social media analysis is crucial to executing informed brand communication strategies. In October 2016, the brand communication strategies of the National FFA Organization were focused on promoting the 89th National FFA Convention. A large portion of these efforts and resources were dedicated towards the utilization of social media. This study was designed as a content analysis of the National FFA Organization’s social media presence during the dates of the convention. The goal was to identify the prominent themes of communication and the alignment of these themes with the organizational brand. Conversations on Facebook, Twitter, Instagram, and Snapchat yielded a total of 344 posts for evaluation. The results indicated the presence of seven predominate themes: recognition, connectivity, appreciation, spirit, service, influence, and support. The researchers suggest opportunities exist for closer alignment between published social media content and the defined organizational and event brands. Specific attention should be placed on event-specific theme promotion. Renewed efforts to increase interactivity will allow for stakeholders to take part in the brand co-building process. It should be ensured that all communications are an accurate reflection of the brand’s image, connections, and reputation.
Keywords: social media; brand; content analysis; organization; case study